Acute hamstring injuries in Swedish elite sprinters and jumpers: a prospective randomised controlled clinical trial comparing two rehabilitation protocols - Askling, C. M.; Tengvar, M.; Tarassova, O.; Thorstensson, A. (British Journal of Sports Medicine, 2014)
Background: Hamstring strain is a common injury in sprinters and jumpers, and therefore time to return to sport and secondary prevention become of particular concern. Objective: To compare the effectiveness of two rehabilitation protocols after acute hamstring injury in Swedish elite sprinters and jumpers by evaluating time needed to return to full participation in the training process. Study design: Prospective randomised comparison of two rehabilitation protocols. Methods: Fifty-six Swedish elite sprinters and jumpers with acute hamstring injury, verified by MRI, were randomly assigned to one of two rehabilitation protocols. Twenty-eight athletes were assigned to a protocol emphasising lengthening exercises, L-protocol, and 28 athletes to a protocol consisting of conventional exercises, C-protocol. The outcome measure was the number of days to return to full training. Re-injuries were registered during a period of 12 months after return. Results: Time to return was significantly shorter for the athletes in the L-protocol, mean 49 days (1SD±26, range 18-107 days), compared with the C-protocol, mean 86 days (1SD±34, range 26-140 days). Irrespective of protocol, hamstring injuries where the proximal free tendon was involved took a significantly longer time to return than injuries that did not involve the free tendon, L-protocol: mean 73 vs 31 days and C-protocol: mean 116 vs 63 days, respectively. Two reinjuries were registered, both in the C-protocol. Conclusions: A rehabilitation protocol emphasising lengthening type of exercises is more effective than a protocol containing conventional exercises in promoting time to return in Swedish elite sprinters and jumpers.